REDEFINING THE FUTURE OF THE ACCOUNTING PROFESSION: EMBRACING THE INNOVATIVE OPTION OF BLOCKCHAIN TECHNOLOGY (Journal of Global Accounting, 2025)
A cursory look at the accounting profession and how best to reposition it for the demands of the fourth industrial revolution motivated this study. Specifically, the primary objective of this study was to determine the effect of block chain technology on the accounting profession. The paper adopted descriptive research design, relying mainly on primary data extracted from the responses of 263 professional Accountants in Anambra State through the use of structured questionnaires. Findings emanating from the study proved that block chain technology is vital to the growth of the accounting profession through its critical role in enhancing the quality of financial reporting. The study further revealed its benefits to auditing of firms through its abilities of speed of automation and reduction of resources necessary for audits. Based on these findings, the study suggested converted efforts geared by stakeholders on the full adoption of the technology in all accounting procedures and massive acquisition of technological skills by modern day accountants.
Keywords: Accounting Profession; Block chain Technology; Financial Reporting